Prevalence of Stroke and Hypoperfusion in Patients With Isolated Vertigo and Vascular Risk Factors - Zhang, Dao Pei; Li, Hao Ran; Ma, Qian Kun; Yin, Suo; Peng, Yan Fang; Zhang, Huai Liang; Zhao, Min; Zhang, Shu Ling (Frontiers in Neurology, 2018)
Background and Purpose: The aim of this study was to determine the prevalence and associated factors of stroke and hypoperfusion among patients with isolated vertigo and vascular risk factors. Methods: We studied 157 patients with isolated vertigo who had undergone multimodal magnetic resonance imaging. Magnetic resonance angiography (MRA) was used to measure the diameters of vertebrobasilar arteries and to evaluate morphologic changes to vessels. Measurements obtained included length of the basilar artery and curvature index for the vertebral artery (VA). Perfusion-weighted imaging (PWI) was performed to determine relative cerebral blood flow, relative cerebral blood volume (rCBV), time to peak (TTP), and mean transit time for two mirror regions of interest (ROIs) in each map. Regional hypoperfusion of the cerebellum was considered significant when TTP and mean transit time (MTT) were present in ≥2 adjacent slices. Results: The prevalence of stroke in patients with isolated vertigo and vascular risk factors was 24.8% (n = 39). Visual assessment revealed cerebellar hypoperfusion in 57.6% (68/118) of non-stroke patients. Multivariate logistic regression indicated that diabetes mellitus (P = 0.049, OR = 2.758), VA stenosis or hypoplasia (P = 0.023, OR = 3.486), and relative TTP of cerebellum (P = 0.002, OR = 3.197) were independent risk factors for stroke and LVA curvature index (P = 0.026, OR = 2.049), VA stenosis and hypoplasia (P = 0.009, OR = 2.977) were independent risk factors for hypoperfusion. Conclusions: The prevalence of stroke and hypoperfusion is higher in patients with isolated vertigo and vascular risk factors, compared with matched controls. Potential risk factors include diabetes mellitus, VA stenosis or hypoplasia, and enlarged VA curvature index.